(untitled) (Research, Society and Development, 2023)
Objective: To carry out an integrative review of the literature on the oral health conditions of children and adolescents who are victims of domestic violence. Methodology: An integrative literature review was carried out based on the PRISMA model and based on the following guiding question ’’What are the oral health conditions of children and adolescents victims of domestic violence?’’ MEDLINE/PubMed databases were searched. and LILACS/VHL using the MeSH Child, Adolescent, Domestic Violence and Oral Health descriptors and their Portuguese versions. After selecting the articles by analyzing titles and abstracts, they were read in full and considered the original articles that covered children and adolescents between 0 and 19 years of age. Inclusion and exclusion criteria were also established in the study selection process. Results: Fifteen articles were selected, all with an observational design, 13 of which were analytical (three cohort studies, six cross-sectional, three retrospective studies and one case control) and two descriptive (case reports). Conclusion: Children victims of domestic violence had a higher prevalence of cavities, high levels of dmft/DMFT indexes, worse oral hygiene and low frequency of dental appointments. High rates of tooth extractions, bacterial plaque accumulation, pain and dental infection were also observed. According to the present study, negligence was the main type of violence found when related to oral health.